The Tolerability of the Vaccine against P. aeruginosa in Children with Cystic Fibrosis and Congenital Lung Development - D. A. Blagovidov; M. P. Kostinov; O. I. Simonova; A. D. Shmit'ko; N. I. Burkina; M. K. Shahnazaryan (Эпидемиология и вакцинопрофилактика)
Chronic Pseudomonas aeruginosa infection is the most common cause of the failure in treatment and of adverse outcomes among children with congenital malformation of the lung (CML) and cystic fibrosis (CF). Purpose: To evaluatae the safety of anti Pseudomonas aeruginosa vaccine in children with congenital malformation of the lung and cystic fibrosis. Material and methods: 81 hospitalized children aged 5 to 17 with congenital malformation of the lung and cystic fibrosis participated in the research. 47 patients not experiencing exacerbation during basic therapy were vaccinated with anti Pseudomonas aeruginosa vaccine Pseudovac that consists of structural and extra-cellular antigens of the 8 immunotypes of Pseudomonas aeruginosa. The control group included 34 children who were not vaccinated, and had P. aeruginosa acquisition or infection. All the patients were under observation for the period of one year. Results: Pain in the injection site was registered in 74.5% and 76.6% of cases after the first and the second administration respectively. Further injections (3rd, 4th and 5th) of the vaccine caused much less local pain. In the majority of cases pain was mild and disappeared without medication within 24 hours. Redness in the injection site was registered in 29.8% of cases after the second administration of the vaccine. After further injections it was significantly less common. Local swelling in the injection site of not more than 25 mm after the first injection of the vaccine was registered in 57% of the cases, and in 100% of the cases after the second injection. It lasted less than 24 hours. Among vaccinated patients fever up to 37.5 degrees Celsius was registered in 23,4% of the cases. And up to 38.5 degrees in 4,3% of the cases. The reaction was observed within two hours after the injection and appeared regardless of the number of administrations lasting no longer than 24 hours. There appeared other single general reactions such as headache, dizziness or dry cough lasting up to 6 hours.